GAMBARAN PENGETAHUAN ORANG TUA TENTANG KESEHATAN REPRODUKSI REMAJA RETARDASI MENTAL - Handayani, Nur; Yati, Dwi (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2020)
Adolescence is a transition between childhood and adulthood, where changes and development occur, including the development of reproductive organs. Reproductive health problems that may be experienced by adolescents include unwanted pregnancy, sexually transmitted diseases, and the problem of limited access to information. The introduction of the reproductive system for adolescents is the responsibility of parents, so parents must have sufficient knowledge about adolescent reproductive health.The purpose of this study was to determine the description of parents' knowledge about adolescent reproductive health mental retardation in SLB C Wiyata Dharma 2 Sleman.This research is a quantitative descriptive study with cross sectional design. The study was conducted in June 2019. The population in this study were adolescent parents of mild or moderate mental retadation in SLB C Wiyata Dharma 2 Sleman as many as 43 respondents. The sample consisted of 43 parents, taken with a total sampling technique. Data collection tool is a questionnaire. Data were then analyzed using frequency distribution and cross tabulation.The results showed that the majority of respondents had good knowledge as much as (74.4%). Where respondent who have goog knowledge are mostly aged 36-45 years (35%), with education background high school / vocational (48.9%), work privately (30.2%) and get information about reproductive health (72.1%), most information obtained from the internet (40%).Parents' Knowledge of Adolescent Reproductive Health in SLB C Wiyata Dharma 2 Sleman in the good category.